2018
DOI: 10.14744/anatoljcardiol.2018.98250
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Tp−Te Interval, Tp-e/QTc ratio and QT Dispersion in Patients with Turner Syndrome

Abstract: Objective:To evaluate ventricular repolarization parameters using the interval from the peak to the end of the T wave (Tp–Te), together with QT and corrected QT (QTc) intervals, QT dispersion (QTd), and Tp-Te/QTc ratio in patients with Turner syndrome (pwTS) and to compare the results with those from healthy controls.Methods:In total, 38 patients previously diagnosed with Turner syndrome (TS) and 35 healthy girls (controls) were included in our cross-sectional study. Twelve-lead electrocardiography (ECG) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
10
0
2
Order By: Relevance
“…Several studies have analyzed the QTc interval in patients with TS and POI, though with many limitations [ 59 , 60 ]. These studies were from a small number of patients with only limited data on HRT and most without hormonal evaluation.…”
Section: Qtc Variation In Hypoestrogenic and Hyperandrogenic Statementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have analyzed the QTc interval in patients with TS and POI, though with many limitations [ 59 , 60 ]. These studies were from a small number of patients with only limited data on HRT and most without hormonal evaluation.…”
Section: Qtc Variation In Hypoestrogenic and Hyperandrogenic Statementioning
confidence: 99%
“…Moreover, QTc was frequently calculated with Bazett’s formula that does not take into account the higher heart rate in TS as with the use of Hodge’s formula, which is the preferred QTc correction in these patients [ 56 ]. In a recent cross-sectional study, Atici et al demonstrated that 38 patients with TS had significantly longer QTc than 35 controls (respectively, QTc 411.9 ± 22.7 vs. 392.1 ± 13.2 ms, p < 0.001), with the major limitation being the lack of data on karyotype or hormonal treatment [ 60 ]. This lengthening of the QTc interval had already been highlighted by Bondy et al as early as 2006 [ 61 ].…”
Section: Qtc Variation In Hypoestrogenic and Hyperandrogenic Statementioning
confidence: 99%
“…В первую очередь, это показатели реполяризации желудочков: удлинение интервала QT, который зависит от вариабельности реполяризации желудочков и, возможно, дисперсия интервала QT (QTd). Показано, что увеличения значений QT и QTd ассоциированы с повышенным риском аритмической смерти [43]. Также довольно ценным в аспекте прогнозирования внезапной сердечной смерти является определение показателя микровольтной альтернации зубца Т [44,45].…”
Section: проаритмические эффекты препаратов применяемых для лечения Covid-19unclassified
“…Besides cardiovascular malformations, electrocardiogram (ECG) abnormalities, mainly QTc prolongation, have been reported (Atici et al, 2018 ; Bondy, Ceniceros, et al, 2006 ; Bondy, Van, et al, 2006 ; Dalla Pozza et al, 2006 ; Dalla Pozza et al, 2009 ; Sozen et al, 2008 ; Trolle et al, 2013 ). We recently found no increased prevalence of QTc prolongation using Hodges formula in a large cohort of girls ( n = 101) and women ( n = 251) with TS, as was confirmed by Harrahill et al in 112 women with TS (Harrahill et al, 2020 ; Noordman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%